EP022/#229 Non-mammary breast metastases: a clinico-pathological study. (4th December 2022) - Hamida, Karim Ben; Houcine, Yoldez; Maaoui, Amal; Hamza, Khedija; Kamoun, Salma; Hmidi, Amira; Ayadi, Senda; Chargui, Riadh; Driss, Maha
Abstract : Objectives: We aimed to evaluate non-mammary breast metastases, and to precise their clinico-pathological and follow-up characteristics. Methods: We identified 17 patients diagnosed with non-mammary breast metastases between 2006 and 2021 at Salah Azaiez Institute of Oncology. Histological slides were reviewed. Clinico-pathological characteristics and follow-up data were retained from medical files. Results: Seventeen patients were included in our study (three men and fourteen women). The median age at diagnosis was 44 years (17–65 years). The most common presentation was a palpable mass (50%). The metastases were unifocal, and the median size of the metastatic focus was 12 mm. The most common metastatic neoplasia was lymphoma (43, 8%) (90% diffuse large B-cell lymphoma and 10% Hodgkin lymphoma). It was followed by melanoma (17, 6%), mostly cutaneous, leiomyosarcoma (15%), undifferentiated carcinomas of nasopharyngeal type (11, 6%), neuroendocrine tumor (6%, mostly from the gynecologic tract) and fibrosarcoma (6%). The diagnoses were confirmed by immunohistochemistry in 75% of cases. Breast metastases were unique in 15% of patients and associated with other organ metastases in 85% of patients. The median time of follow-up from the breast metastasis event to the last follow-up was 12 months. The median overall survival after BM diagnosis was 24 months (1 month-13 years). Conclusions: In our series, the most common tumor type was lymphoma, followed by melanoma. The diagnosis of metastases from primary breast lymphoma may be challenging, especially when the metastasis is unique. The initial clinico-radiological correlation may be very helpful to identify metastases and provide optimal patient care.